PENENTUAN KOMPOSISI WAKTU OPTIMAL PRODUKSI DENGAN METODE TAGUCHI (Studi Kasus: Penelitan di Pabrik Kerupuk Rambak Stik Cap Ikan Bawang, Semarang) - Angga Saputra Desti; Triastuti Wuryandari; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Many businesses crackers facing obstacles in meeting the market demand. Business doers must minimize time in the process so that market demand can be fulfilled. This study aims to minimize the time making process as well as getting the right optimal composition without damaging the quality of the product. Settlement problems using the Taguchi method in experimental design . Factor used is steaming (22 and 19 minutes), the first drying (7 and 6 hours), the second drying (10 and 9 hours) and frying (2 minutes 45 seconds and 2 minutes 30 seconds), as well as variables assessed from the experimental results in terms of taste, color and crunchiness with using organoleptic assessment by a not trained panelists. From the experimental results best factor level selected by SNR and the mean value in terms of taste, color and crunchiness. The composition of the optimal cracker manufacture process to produce the most preferred crackers elected steaming (19 minutes), the first drying (7 hours) , the second drying (9 hours) and frying (2 minutes 30 seconds). Optimal composition of the comparison results with the standard factory based T – test independent sampel the response of taste, color and crunchiness produce the same average, with the time difference for once the process is 310 minutes or 5 hours 10 minutes.